Tree clusters migration into alpine tundra, Siberia - Kharuk, Viacheslav I.; Petrov, Ilya A.; Im, Sergei T.; Golyukov, Alexey S.; Dvinskaya, Maria L.; Shushpanov, Alexander S. (Journal of mountain science)
We hypothesize that in mountain windy habitat trees formed clusters (hedges) as adaptive structures for seedlings’ rooting, survival, and tress’ upslope migration. We studied hedges formed by Siberian pine (Pinus sibirica du Tour) and larch (Larix sibirica Ledeb.) within the treeline ecotone in southern Siberian Mountains, investigated hedges formation, evolution, habitat amelioration, and analyzed tree’s growth index (GI) dependence on the eco-climate variables (air temperature, precipitation, soil moisture, wind speed) and relief features (elevation, aspect, slope steepness, and terrain curvature). We conducted a ground survey, measured biometrical parameters of trees and hedges, determined species composition and tree physiognomy, soil types and nutrient contents, and sampled wood cores and applied dendrochronology for trees’ GI analysis. With high-resolution satellite scenes for hedge detection and upslope migration, we found that winter winds and soil moisture are the main constraints of trees’ settlement and growth. Hedge formation always links with wind-sheltered microtopography features (boulders, local depressions or felled trees). Once the first tree is established, a positive feedback is aroused that facilitates seedling rooting and in-hedge habitat amelioration. Trees form a streamlined dense “common crown” that mitigates adverse winter wind influence. Hedges always orient along the prevailing winds, and trees’ uphill migration occurs by seedlings establishment within the leeward hedge side. Hedge growth facilitates soil formation and fertilization. The concentration of nutrients (K, P, N and S) within hedges exceeds the background by 1.5–5.5 times. Hedge extension leads to increased snow accumulation that mitigates the influence of desiccation and snow abrasion and mitigates seasonal water stress. In the extremely harsh windy habitat, in-hedge trees present in mat, prostrate or krummholz forms. With warming, tree stems and even twigs turn upright. Notably that GI dependence on the wind speed is insignificant until prostrated trees get turning upright. Since that, the negative correlation between GI and wind speed is arisen with subsequent decrease since hedges form streamlined crown. Hedge growth also leads to a “phytofield” formation (i.e., grasses, lichen, moss and small bushes growth) around the hedges that, in its turn, encourages seedling rooting which is about triple more efficient than outside the phytofield. Larch, in comparison with Siberian pine, is less often formed hedges. GI of both species is stimulated by warmer air temperature in the beginning of the growth season. Meanwhile, larch GI has stronger response to elevated temperatures and less dependent on soil moisture. This indicates larch is a potential substitute of Siberian pine in a warmer and dryer climate. Hedges in warming climate evolve into closed stands due to both in-hedge tree growth and filling gaps between hedges by different tree species.